2021
DOI: 10.1051/e3sconf/202127313007
|View full text |Cite
|
Sign up to set email alerts
|

Rationale for the formulation of fortified detox biscuits

Abstract: Nowadays, most manufacturers are strategically focused on making healthy food products. Flour confectionery is a promising group of food products in this respect. The expansion of the range of flour products is due to the introduction of additional raw materials, one of the options for which is pectin. The aim of the research is to study the effect of different types of pectin on the detoxifying properties of biscuits and their quality indicators. The objects of research are three types of pectin (beet, apple,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…In addition, Fang et al (2022) reported that there was no significant difference in the spread ratio and color compared to the control, resulting in a product with improved nutritional value and comparable quality. In a study conducted by Sokol et al (2021), the effects of high‐methoxy P from three different sources, such as apple, watermelon, and beet, on biscuits were compared. The findings indicated a decrease in the moisture content and enhanced thickening ability, both of which are positive factors contributing to improvement of the overall quality.…”
Section: Chemistry Rheology and Food Application Of Fibers In Bakery ...mentioning
confidence: 99%
“…In addition, Fang et al (2022) reported that there was no significant difference in the spread ratio and color compared to the control, resulting in a product with improved nutritional value and comparable quality. In a study conducted by Sokol et al (2021), the effects of high‐methoxy P from three different sources, such as apple, watermelon, and beet, on biscuits were compared. The findings indicated a decrease in the moisture content and enhanced thickening ability, both of which are positive factors contributing to improvement of the overall quality.…”
Section: Chemistry Rheology and Food Application Of Fibers In Bakery ...mentioning
confidence: 99%